Immunization with recombinant enolase of Sporothrix spp. (rSsEno) confers effective protection against sporotrichosis in mice - Portuondo, Deivys Leandro [UNESP]; Dores-Silva, Paulo Roberto; Ferreira, Lucas Souza [UNESP]; de Oliveira, Carlos S.; Téllez-Martínez, Damiana [UNESP]; Marcos, Caroline Maria [UNESP]; de Aguiar Loesch, Maria Luiza [UNESP]; Guzmán, Fanny; Gava, Lisandra M.; Borges, Júlio César; Pereira, Sandro Antonio; Batista-Duharte, Alexander [UNESP]; et al. (Springer Nature, 2019)
In recent years, research has focused on the immunoreactive components of the Sporothrix schenckii cell wall that can be relevant targets for preventive and therapeutic vaccines against sporotrichosis, an emergent worldwide mycosis. In a previous study, we identified a 47-kDa enolase as an immunodominant antigen in mice vaccinated with an adjuvanted mixture of S. schenckii cell wall proteins. Here, we sought to assess the protective potential of a Sporothrix spp. recombinant enolase (rSsEno) formulated with or without the adjuvant Montanide Pet-GelA (PGA) against the S. brasiliensis infection in mice. Mice that were immunized with rSsEno plus PGA showed increased antibody titters against rSsEno and increased median survival time when challenged with S. brasiliensis as compared with mice that had not been immunized or that were immunized with rSsEno alone. Immunization with rSsEno plus PGA induced a predominantly T-helper 1 cytokine pattern after in vitro stimulation of splenic cells with rSsEno: elevated levels of IFN-γ and IL-2, as well as of other cytokines involved in host defense against sporotrichosis, such as TNF-alpha, IL-6, and IL-4. Furthermore, we show for the first time the presence of enolase in the cell wall of both S. schenckii and S. brasiliensis. As a whole, our results suggest that enolase could be used as a potential antigenic target for vaccinal purposes against sporotrichosis.